The importance of DHEA in sexual health during menopause - Grażyna Jarząbek-Bielecka; Katarzyna Plagens-Rotman; Witold Kędzia; Urszula Religioni; Piotr Merks (Polish Pharmaceutical Society, 2020)
The cause of psychosexual problems among men and women during menopause are changes in not only the hypothalamic-pituitary-gonadal axis but also the deficiency of the endogenous steroid hormone DHEA (dehydroepiandrosterone), which increases with age. DHEA deficiency causes mental, physical and psychosexual ailments related to men and women with menopause. Although sexual reactions are strongly modified by psychogenic factors (emotional attitude towards a partner, attitude towards one's own body and body, general mood, feeling of happiness, satisfaction with life), hormonal and neuroendocrine factors also have a significant influence here. DHEA significantly affects the concentration of sex hormones. Optimal high estrogen concentration in women affects, among others on vascularization and blood flow within the vagina, and progesterone affects, among others on the regulation of sexual function in the central nervous system (CNS). At the same time, more than half of menopausal women observe signs related to vaginal epithelial atrophy manifested by a feeling of dryness, pain during sexual intercourse or recurrent infections in the genital area. In turn, during andropause, i.e. male menopause, there is a gradual physiological decrease in the level of testosterone in the blood, which results in a reduction of sex drive, the occurrence of erection problems, decreased sexual activity, and decreased satisfaction with intercourse. This article aims to review issues related to sexual health, along with an indication of the complexity of regulatory mechanisms that control sexual responses. The article highlights, in particular, the supportive effect of DHEAS in the treatment of age-related sexual dysfunction in both sexes. In the care of patients, the importance of cooperation between the doctor and the pharmacist and the role of pharmacy counselling were emphasized. The implementation of new pharmaceutical services in the field of developing a sexual health education model, such as the Erectile Disfinction Program, carried out in many countries around the world, maybe an important element of the strategy of patient support at national and local levels.